A phylogenetic analysis of the tent tortoise Psammobates tentorius (Bell, 1828) species complex, using molecular and morphological markers - Zhao, Zhongning (University of the Free State, 2019)
The rapid development of advanced DNA analytical programs, algorithms and techniques have greatly strengthened molecular systematics in the discovery and clarification of biodiversity, as well as the accuracy of taxonomies and reconstructing the relationships among taxa or operational taxonomic units (OTUs). Furthermore, these sophisticated analytical approaches enhanced traditional systematic biology in terms of temporal and spatial dimensions, thereby bridging the gap between the past, present and future. Phylogeographical analyses allow proper interpretation of how the distribution of organisms correlates with their cladogenesis, while biogeographical analyses enable the determination of how changes in geographic features and systematics are correlated. Lastly, utilizing molecular markers in calibration dating with sophisticated current analytical models enable the tracing of radiation histories, while diversification rate analyses allow the predicting of likely future cladogenic scenarios, which are crucial for conservation management. Modern molecular systematics also makes possible the testing of alternative phylogenetic reconstruction scenarios via computational simulations. All these methodological advances overcome the limitations of traditional phylogenetic analysis in developing evolutionary and cladogenic scenarios, and strengthen our ability to predict and prepare for likely future biodiversity patterns. Chapter 1 provides the general introduction to the study, which focused on the highly polymorphic and taxonomically confusing tent tortoise (Psammobates tentorius) (Testudines: Testudinidae) species complex from southern Africa and had six broad objectives. First, to identify its clades and infer phylogenetic relationships among them, using mitochondrial and nuclear DNA sequence data, as well as microsatellite DNA data. Second, to use the phylogenetic assumptions to delineate the clades into a proper OTUs scheme, which will be crucial for the taxonomic revision of the complex. Third, to elucidate the radiation history of the complex against temporal and spatial parameters, using phylogeographic and biogeographic analyses. And then to use diversification rate analyses to elucidate cladogenic rates and predict future radiation trends, which could benefit conservation management efforts. Fourth, using DNA markers to determine genetic structure and diversity between and within clades, which should also benefit the conservation of the complex. Fifth, to use computational simulations to determine alternative systematics scenarios, which could potentially explain the radiation history from a more explicit evolutionary viewpoint. Sixth, to use morphometric measurements and morphological character analyses to find diagnostic characters for the different candidate species needed for reviewing the taxonomy of the species complex. Chapter 2 reports on the investigation of genetic structure, phylogenetic relationships and genetic diversities within the P. tentorius complex, which resulted in the discovery of seven clades (C1-C7). The mtDNA and nDNA datasets generated conflicting tree topologies. The mtDNA dataset retrieved seven clades, each associated with a distinct geographic region. The nDNA dataset advocated three lineages generally corresponding with the three currently recognized subspecies, although potential hybridization was found between C1 and C2, and between C2 and C4. The multiple species delimitation analyses and the traditional p-distance method generally supported 6 to 7 putative species corresponding to the seven clades, although most of the analyses suggested six putative species. It was found that the currently recognized Psammobates tentorius verroxii was not a monophyletic group, but consisted of two candidate species, so its current taxonomic status should be revised. The uniformly brown coloured “Psammobates bergeri” mentioned in the literature should not be considered a valid taxon, since it has been found in three clades. The “Psammobates tentorius trimeni”- like population found in the Kamiesberg, Hantam Karoo and Roggeveldberge region is genetically the close relative of C1, but distant relative of the real P. t. trimeni occurring on the west coast of South Africa. The findings in Chapter 3 suggest that divergence in the P. tentorius complex is deep, with most of the cladogenic events occurring in the Miocene, while radiation within the species is linked to the Pliocene and Pleistocene. The results of the biogeographic, diversification rate and character dependency analyses suggest that the cladogenic radiation of the P. tentorius complex was shaped by climatic and topographic changes since the Miocene. The calibration dating results revealed that the cladogenic divergences in the P. tentorius complex were comparable to that found in many other genera. This implies that some of the clades may deserve to be elevated to species level. Chapter 4 reports on the comparison of the phylogenetic topologies generated from the nDNA, mtDNA, mtDNA+nDNA and microsatellite DNA datasets. The results showed that the tree topologies did not differ greatly between the sequence and microsatellite datasets, despite the incongruence between the mtDNA and nDNA datasets as indicated in Chapter 2. The Bayesian computational simulation results advocated an alternative systematic scenario, different from the best scenario retrieved with the traditional phylogenetic analyses. It was found that this scenario more plausibly explained the cladogenic prosesses of the P. tentorius complex. The microsatellite based multivariate analyses and clustering analyses generally suggested 4-6 putative species for the complex, with the difference between C1 and C4 not clear. The findings are generally congruent with the phylogenetic and species delimitation results reported for the sequence datasets in Chapter 1. Chapter 5 reports on the use of selection analysis, based on codon and dN/dS ratios in the protein coding genes Cyt-b, ND4 and PRLR. The results suggested a unique selection pattern for group C2+C3, which is believed to have been driven by intensification of aridity during the development of the Benguela Current, 8-10 Mya. However, the dN/dS-based assumption should only be regarded as a reasonable assumption or hypothesis, as further long-term ecological experiments or simulations based on historical climate datasets are needed to investigate the real scenario. No new putative species were detected by the phylogenetic inference using codon and amino acid datasets. Nonetheless, codon-based phylogeny, transition and transversion rate-based topologies and phylogenetic reconstruction using amino acid sequences provided additional support for confirming the validity and stability of the seven clades. Chapter 6 should be considered as preliminary, as sufficient samples of C5, C6 and C7 could not be obtained to allow reliable morphometric and phenotypic analyses. Despite the inadequate and uneven samples, the results still showed clear sexual dimorphism, and also suggested that morphological characters could be used to distinguish among the clades. The discrete (phenotypic) and continuous (morphometric) character datasets both showed clear separation between the two major branches “C1+C4+C5+C7” and “C2+C6”. Four clusters were distinguishable: C2, C3, C6 and (C1+C4+C5+C7). These results showed a good match with the microsatellite DNA results of Chapter 4. Chapter 7 is the concluding chapter which summarizes the findings of the study along with recommendations.
Thesis (Ph.D. (Zoology and Entomology))--University of the Free State, 2019
Keywords: DNA -- Evolution; Tortoise -- (Psammobates tentorius); Phylogeographical analyses; Morphological markers; Molecular markers